Increased microalbuminuria prevalence among patients with nonalcoholic fatty liver disease. (2nd January 2016) - Kasapoglu, Benan; Turkay, Cansel; Yalcın, Kadir Serkan; Boga, Salih; Bozkurt, Alper
Abstract: Aim : To determine the prevalence of microalbuminuria, that is an indirect predictor of coronary artery disease, among non-obese and non-diabetic patients with fatty liver disease. Material and method : This retrospective study was carried out on non-obese (body mass index (BMI) < 30) and non-diabetic 290 female and 189 male, totally 479 cases. All subjects underwent liver ultrasonography scanning to determine the presence and stage of fatty liver disease. Results : The subjects were grouped according to the ultrasound findings as follows: 182 (37.9%) cases without any fat accumulation in liver were regarded as control group; and among remaining cases, 124 (25.8%) had mild, 93 (19.4%) had moderate, and 80 (16.7%) had severe fatty liver disease. There was not any statistically significant difference between groups in regards to the age, gender, liver function tests, renal function tests or glomerular filtration rate. However urinary protein/creatinine ratio was statistically significantly higher in severe nonalcoholic fatty liver disease (NAFLD) group than the other three groups. In moderate and severe NAFLD groups, microalbuminuria was statistically significantly more common compared with the control and mild NAFLD groups. Regarding the results of multiple logistic regression analysis, presence of fatty liver disease increased the risk of microalbuminuria for 1.87 times independently from increased BMI and increased HOMA-IR values. Conclusion : We have determined that microalbuminuria is more prevalent among NAFLD cases compared with control cases and microalbuminuria prevalence was increasing with the advanced stages of NAFLD although two main etiologic factors of microalbuminuria, type 2 diabetes, and obesity were excluded.